Iraq and the Politics of Oil : An Insider's Perspective - Vogler, Gary (Book collections on Project MUSE., 2017)
In this book, Gary Vogler tells the story of US involvement in the Iraq oil sector from 2002-2011. Vogler, a 21-year Mobil Oil and ExxonMobil employee, was an insider who was involved in the prewar planning stages and spent over six years in Iraq as a member of the Energy Infrastructure Planning Group (EIPG) and later as a senior oil advisor in the Office of Reconstruction and Humanitarian Affairs (OHRA). Vogler's book was originally going to be a tribute to the great work he saw from US forces. But in the course of his research, and in looking back on his sometimes tense interactions with Department of Defense and White House staff, Vogler came to understand the darker political side of the role of oil in the decision to go to war with Iraq. It was not, as many thought, merely to secure a steady, indefinite supply of Iraqi oil for the US market, or to secure contracts for US oil companies. The purpose was in fact grander--to rebalance the political map of the Middle East by providing a steady supply of oil to Israel through the Kirkuk-Haifa pipeline, and deny oil to Syria, a purpose which was designed to enrich and empower various international operators in the region who operated below the radar on the periphery of the war effort.